Numerical evaluation for the effective slab width of steel-concrete composite beams. (September 2018) - Lasheen, Mahmoud; Shaat, Amr; Khalil, Ayman
Abstract: Although several studies in the field of steel-concrete composite beams reported that the effective concrete slab width depends on the loading stage of such beams (i.e. serviceability and ultimate stages), international codes have not considered it yet. In this respect, a nonlinear finite element model was developed using ABAQUS 6.10 and validated using three independent experimental research programs. The model was found capable of predicting the behavior of such beams and hence calculating a more accurate effective slab width. An extensive parametric study is conducted on 222 beams to evaluate the effective slab widths at service and ultimate loads. Different parameters related to beams geometry and concrete slab material were considered in this study. The results of this study showed that the effective width depends on the slenderness ratio (L/rs ) of the steel beam and the slab width-to-span ratio (Bs /L). In addition, it is found that the effective width at ultimate load is wider than that at service load. Finally, two sets of equations are provided to calculate the effective width at service and ultimate load. The provisions of the ANS/AISC 360–10 for the effective width were compared with the prediction presented herein. Highlights: An extensive parametric study is conducted to evaluate the effective slab widths at service and ultimate loads. The effective slab width depends on the slenderness ratio (L/rs ) of the steel beam and the slab width-to-span ratio (Bs /L). The effective slab width at ultimate load is wider than that at service load. Two sets of equations are provided to calculate the effective width at service and ultimate loads.